Relationship between parental psychological control and problem behaviours in youths: A three-level meta-analysis. (May 2020) - Yan, Fuyun; Zhang, Qi; Ran, Guangming; Li, Song; Niu, Xiang
Highlights: Problem behaviours in children and adolescents. A significant positive association between parental psychological control and youths' problem behaviours. The significant moderating effects of youths' age and informant of parental psychological control. Abstract: Background: Problem behaviours in youths (children and adolescents) are considered serious risk factors for the development of behavioural, psychological and psychiatric problems in adulthood. Even though numerous studies have shown that parental psychological control is positively related to youths' problem behaviours, others have failed to detect a significant association between these two variables. Methods: Employing the PRISMA method, the present study employed a three-level meta-analysis to obtain reliable estimates of the effect sizes and examine a range of moderators. Results: In total, 25 studies including 7996 young people and 137 effect sizes were obtained based on a comprehensive literature search. The analysis revealed a significant positive association between parental psychological control and youths' problem behaviours. In addition, there were significant moderating effects of youths' age and informant of parental psychological control on the association between parental psychological control and youths' problem behaviours. Conclusions: In sum, this review helps to elucidate the association between parental psychological control and youths' problem behaviours.